Hypocalcaemia and vitamin D deficiency: an important, but preventable, cause of life-threatening infant heart failure. Issue 5 (9th August 2007) - Maiya, S; Sullivan, I; Allgrove, J; Yates, R; Malone, M; Brain, C; Archer, N; Mok, Q; Daubeney, P; Tulloh, R; Burch, M
Abstract : Background: In recent large paediatric cardiomyopathy population studies from North America and Australia, vitamin D deficiency was not identified as a cause of infant heart failure. However, rickets is resurgent in developed countries. Objective: To review the prevalence of this cardiomyopathy in paediatric cardiology units of southeast England and determine the prognosis. Methods and results: A retrospective review from 2000 to 2006 in southeast England. Sixteen infants (6 Indian subcontinent, 10 black ethnicity) were identified: median (range) age at presentation was 5.3 months (3 weeks–8 months). All had been breast fed. Ten presented at the end of the British winter (February–May). Median shortening fraction was 10% (range 5–18%) and median left ventricular end diastolic dimension z score was 4.1 (range 3.1–7.0). Six had a cardiac arrest; three infants died. Eight were ventilated, two required mechanical circulatory support and 12 required intravenous inotropic support. Two were referred for cardiac transplantation. Median (range) of biochemical values on admission was: total calcium 1.5 (1.07–1.74) mmol/l; alkaline phosphatase 646 (340–1057) IU/l; 25-hydroxyvitamin D 18.5 (0–46) nmol/l (normal range >35) and parathyroid hormone 34.3 (8.9–102) pmol/l (normal range <6.1). The clinical markers and echocardiographic indices of all survivors have improved. The mean time from diagnosis to achieve normal fractional shortening was 12.4 months. Conclusions: Vitamin D deficiency and consequent hypocalcaemia are seen in association with severe and life-threatening infant heart failure. That no infant or mother was receiving the recommended vitamin supplementation highlights the need for adequate provision of vitamin D to ethnic minority populations.